Needs of Parents and Neonates in the Intensive Care Unit: A Literature Review - Qualls, Brandon W. (American Journal of Perinatology, 2025)
The admission of a neonate to the neonatal intensive care unit (NICU) presents unique and complex needs for both the infant and their parents. This literature review aims to synthesize existing research to comprehensively understand these needs, focusing on parental psychosocial well-being, practical requirements, and the neonate's developmental necessities. Understanding these needs is crucial for optimizing clinical outcomes and fostering healthy parent-infant relationships. A nonsystematic literature review was conducted using PubMed, Google Scholar, and PsycINFO databases. Search criteria focused on “neonatal intensive care” and “parental needs.” Articles published in English between 2011 and 2022 were included. The review analyzed 123 articles, primarily focusing on research conducted in Western countries. Parental needs were categorized into seven areas: mental health/psychosocial well-being, practical needs (physical, safety, monetary), parental involvement, relationships (infant, staff, peers), information, spiritual needs, and help with other responsibilities. Neonatal needs included parental involvement, skin-to-skin contact, breastfeeding, and reduced length of stay. Key findings highlighted the prevalence of parental anxiety and depression, the importance of practical support, and the critical role of parental involvement in both parent and infant well-being. This review underscores the interconnectedness of parental and neonatal needs within the NICU environment. Parental involvement is essential for both groups, and factors such as hospital policies, community resources, and socioeconomic status significantly influence fulfilling these needs. The limitation of the review indicates the need for more diverse global research. Future studies should address these limitations and explore effective interventions to meet the identified needs, improving outcomes for NICU families.
Keywords: literature review; neonatal intensive care unit; parental needs; neonatal needs